A experiência da participação de mulheres em grupos de apoio na vivência do parto - Ferreira, Graziani Izidoro (Universidade Federal de São Carlos, 2015)
Historically, delivery care was practiced by midwives. However, from the 40's, childbirth has become institutionalized in an attempt to contain the high levels of maternal and child mortality. These transformations away from the birth process family, subjecting women to institutionalists and interventionist practices. Social movements in favor of the physiological birth rescue have struggled to reverse this reality. This research was conducted in São Paulo in the period from 2012 to 2014 and used the Communicative Methodology as a methodological plan that aims not only to describe or explain the reality, but to understand it and interpret it to transform it according to the needs identified. Participants were women who had lived the experience of childbirth, after participating in support groups. The objective was to analyze the satisfaction or not the women who participated in support groups during pregnancy with the birth experience, birth and care received. The data collection instrument was the communicative and report on an analysis of the data was carried out together with the participants, following the methodological rigor. The main elements transformers and obstaculizadores, related to the world of life and the system, guided by the theoretical and methodological framework were identified. The highlight of transforming elements were: feelings and sensations during pregnancy and family support, preparation for delivery and support group as a source of knowledge. The obstaculizadores elements highlighted were: lack of family support, the normal delivery idealization and frustration for the realization of CS and support group focused on the perfect delivery. Therefore, we noted that the system has contributed little to social change, and also has served as hinders element for social transformation birth culture in our country. Therefore, we conclude that feelings and sensations that women face during pregnancy need to be explored and shared to enable the overcoming of those who are negative. Family support is of fundamental importance, as well as the preparation for delivery and support group during pregnancy, as they provide knowledge and security to women regarding birth. We believe that support groups can be mobilized by the experiences of women with their deliveries, acquired in the world of life. This mobilization permeates the interaction and performance of all the experiences in order to make the not successful fuel to overcome the obstacles.
Keywords: Parto (Obstetrícia); Assistência à saúde; Satisfação do paciente; Educação em saúde; Birth; Health care; Patient satisfaction; Health education; CIENCIAS DA SAUDE::ENFERMAGEM